PERANAN GURU PENDIDIKAN KEWARGANEGARAAN DALAM MENCEGAH KENAKALAN PESERTA DIDIK MAS DARULULUM KUALA DUA - Ita Mayasari; Bambang Budi Utomo; Shilmy Purnama (Universitas Tanjungpura, 2020)
Abstract This aim of this reaseach was get information about ’the role of the education teacher of pendidikan kewarganegaraan to prevent the deliquency of student at MAS Darul Ulum Kuala Dua”. The method of the research was observation research with a form of quantitative research. The informant of the research is the teacher of pendidikan kewarganegaraan, Headmaster, student reapresentative, and the ten grades student of natural sciences and social sciences. Male students which amount to 15 student as a samples. The data that has been obtained in this research was processed with data analysis technique with usinng three phases namely redukation data, presentation of data, conclusions and verification. The result of this research was : 1. The role of the teacher of pendidikan kewarganegaraan in preventing deliquency of students is: as a supervisor, as role models for students, as a motivator, and as a communicator for students. 2. The obstacle exsperienced for the teacher pendidikan kewarganegaraan to prevent the deliquency of students is factors from the students themselves, family factor,and the neighborhood. 3. The effort from the teacher of pendidikan kewarganegaraan are communicated to students, and gives mental coaching and religious. Keywords: Delinguency of students, Teacher roles, PPKn